2022
DOI: 10.54097/ehss.v5i.2923
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Parenting Style and Self-Esteem in Adolescents

Abstract: This article reviewed the effect of four parenting styles (i.e., authoritative, authoritarian, permissive, and rejecting/neglectful parenting) on self-esteem and psychological outcomes in adolescents, such as well-being, life satisfaction, and school performance. It was found that parenting styles directly impact psychological outcomes. More specifically, a positive parenting style increases the life satisfaction and well-being of young adults. The results of this review also indicate the negative side of inap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Similar findings were also reported between permissive/indulgent parenting and adolescents' self‐efficacy (e.g., Aldhafri, 2011; Keshavarz & Mounts, 2017). The results, however, were rather inconsistent with some studies suggesting no effects (e.g., self‐control, Jabagchourian et al, 2014; self‐efficacy, Tam et al, 2012) or positive effects of indulgent parenting on cognitive abilities (e.g., competence, Garcia et al, 2021; self‐efficacy, Yousaf, 2015). Taken together, the majority of the studies suggested a negative association between indulgent parenting and basic psychological needs satisfaction, self‐control, and self‐efficacy among adolescents, but the findings are not always consistent.…”
Section: Indulgent Parenting and Adolescents' Basic Psychological Nee...mentioning
confidence: 87%
“…Similar findings were also reported between permissive/indulgent parenting and adolescents' self‐efficacy (e.g., Aldhafri, 2011; Keshavarz & Mounts, 2017). The results, however, were rather inconsistent with some studies suggesting no effects (e.g., self‐control, Jabagchourian et al, 2014; self‐efficacy, Tam et al, 2012) or positive effects of indulgent parenting on cognitive abilities (e.g., competence, Garcia et al, 2021; self‐efficacy, Yousaf, 2015). Taken together, the majority of the studies suggested a negative association between indulgent parenting and basic psychological needs satisfaction, self‐control, and self‐efficacy among adolescents, but the findings are not always consistent.…”
Section: Indulgent Parenting and Adolescents' Basic Psychological Nee...mentioning
confidence: 87%
“…Parenting Styles are very stable and do not change much with the environment. Parenting refers to the aspects of raising a child aside from the biological relationship [2]. Parenting Styles can predict children's academic achievement, social development, mental health and behavioral problems, as well as numerous aspects of individual adjustment and development such as personality, self-esteem, self-efficacy, psychological symptoms, behavioral problems, and so on in adults' children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…19 Permissive and authoritative type of parenting styles found to be related with the self-efficacy on the other hand parenting type with authoritative nature exhibited negative correlation with self-efficacy of adolescents. 20 A study was conducted to explore the role of gender in the association of different parenting style, hardiness, and self-efficacy of children. Paternal authoritative parenting is highly connected to hardiness and better self-efficacy in teenagers and adolescents.…”
Section: Review Of Literaturementioning
confidence: 99%